ANALISIS KESTABILITAN LERENG AKIBAT PENGARUH PERUBAHAN KADAR AIR TANAH DENGAN MEMPERGUNAKAN PERANGKAT LUNAK APLIKASI GEOSTUDIO (Studi Kasus : Lereng Padang Mangatas Payakumbuh) - Nofrizal, Nofrizal; Saputra, Ronaldo; febrian, Deo (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Slope stability analysis has a very important role in planning civil constructions. Unstable slopes are very dangerous for the surrounding environment, therefore slope stability analysis is very necessary. The measure of slope stability is known by calculating the size of the safety factor. Where the results of slope stability analysis calculations are influenced by many factors, the large number of factors makes the calculations not easy. These factors include, for example, the condition of the soil in layers, anisotropic shear strength of the soil, flow of water seepage in the soil and so on. The aim of the research is to analyze slope safety factors. The conclusion was drawn that based on the results of the safety factor calculation on the slope conditions of Padang Manggatas, Luak District, Limapuluh Kota Regency using the manual Bishop method, a value of 2.602 was obtained with a slope angle of 60˚, at a loss slope of 30˚ and 45˚ the safety factor values were obtained, namely 4.10˚ and 3.13˚. This value proves that the slope angle affects the safety factor value, where the smaller the slope angle, the greater the safety factor value obtained. Likewise, the greater the slope angle, the smaller the safety factor value obtained. Calculation of the safety factor value analysis on the slope conditions of Padang Manggatas at an angle of 60˚ using Bishop software, the value was not much different from the results of manual calculations using the Bishop method, namely 2.602, likewise at slope angles of 30˚ and 45˚ the safety factor values were 3.72 and 3.151. Based on the results of the safety factor calculation using the Bishop method manually and using Slope software at a slope angle of 60˚, the safety factor value was >1.5, it can be concluded that the slope condition is stable.Key words: slope stability analysis, safety factors, bishop method, slope software